Including a pressure dependent relation between static and dynamic elastic moduli in a Finite Element deformation model of Grímsvötn Volcano, Iceland - Sonja Heidi Maria Greiner; Halldór Geirsson (Volcanica)
Surface deformation is an important tool for studying active volcanoes. Numerical deformation models can consider irregular features like crustal heterogeneity and avoid biases due to oversimplification. Dynamic elastic moduli can be derived from seismic velocities, but the static moduli apply to deformation studies since strain amplitudes and time scales differ. There is however no commonly acknowledged relation between the two. We implemented a Finite Element deformation model for the Icelandic subglacial volcano Grímsvötn, including bedrock topography and a 3D elastic structure. Dynamic elastic moduli, derived from seismic tomography and density structures, were converted into static moduli via an empirical pressure-dependent relation. The model requires a deformation source at 3–4.5 km depth, and a co-eruptive pressure changes of 8–70 MPa to fit deformation observed during the 2011 eruption at Grímsvötn. Larger source depths compared to previous deformation studies show the importance of considering crustal heterogeneity and static moduli in deformation models.